2019
DOI: 10.1177/1120672119858226
|View full text |Cite
|
Sign up to set email alerts
|

Micropulsed diode laser cyclophotocoagulation in recurrent pediatric glaucoma

Abstract: Purpose: To evaluate the intermediate-term efficacy and safety of micropulsed diode laser cyclophotocoagulation in recurrent pediatric glaucoma. Patients and Methods: A prospective interventional study included children <16 years old diagnosed with recurrent glaucoma, attending Mansoura University, during the period from July 2017 to November 2017. Micropulsed diode laser sessions were performed in all the cases. The main outcome was the intraocular pressure reduction with monitoring of complications as sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 21 publications
1
35
0
3
Order By: Relevance
“…Although the case series was too small to show statistical significance, the change in choroidal thickness could be due to an increased uveoscleral outflow after MP‐TLT. Moreover, among the studies that have reported the IOP outcomes 1 or 8 days after surgery, a maximum IOP lowering was often observed from the first week and then the IOP tended to rise, reaching its peak at 1 month (Aquino et al 2015; Abdelrahman & El Sayed 2018; Al Habash et al 2019; Souissi et al 2019; Garcia et al 2020; Magacho et al 2020) or at 3 months (Lee et al 2017; Barac et al 2018; Yelenskiy et al 2018; Elheifney et al 2019; Nguyen et al 2019; de Crom et al 2020; Wong et al 2020). These findings suggest a potential very early effect due to a nonlethal thermal damage to the pars plana of the CB, improving uveoscleral outflow via a therapeutic cellular biochemical cascade.…”
Section: Mp‐tltmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the case series was too small to show statistical significance, the change in choroidal thickness could be due to an increased uveoscleral outflow after MP‐TLT. Moreover, among the studies that have reported the IOP outcomes 1 or 8 days after surgery, a maximum IOP lowering was often observed from the first week and then the IOP tended to rise, reaching its peak at 1 month (Aquino et al 2015; Abdelrahman & El Sayed 2018; Al Habash et al 2019; Souissi et al 2019; Garcia et al 2020; Magacho et al 2020) or at 3 months (Lee et al 2017; Barac et al 2018; Yelenskiy et al 2018; Elheifney et al 2019; Nguyen et al 2019; de Crom et al 2020; Wong et al 2020). These findings suggest a potential very early effect due to a nonlethal thermal damage to the pars plana of the CB, improving uveoscleral outflow via a therapeutic cellular biochemical cascade.…”
Section: Mp‐tltmentioning
confidence: 99%
“…This method could have lead to cyclophotocoagulation, as the total laser application duration was greater than 3 s per site, which is longer than the commonly used transscleral cyclophotocoagulation, despite not using a continuous motion and, therefore, the thermal effect was lower than with the traditional technique. Retreatments: the literature on retreatment is limited. The studies with the highest retreatment rates (≥20%) were those in which the delivered energies were modest (<100 J) (Tan et al 2010; Aquino et al 2015; Elheifney et al 2019; Nguyen et al 2019; de Crom et al 2020; Radhakrishnan et al 2020; Tekeli & Köse 2020) and/or the mean preoperative IOP was too high (>30 mmHg) to reach the success endpoint after a single session (Tan et al 2010; Aquino et al 2015; Elheifney et al 2019; Jammal et al 2019; Preda et al 2020; Tekeli & Köse 2020). Tekeli & Köse (2020) have found a significantly higher retreatment rate in eyes with other types of secondary glaucoma than in eyes with POAG and PXG.…”
Section: Mp‐tltmentioning
confidence: 99%
“…Therefore, this modality is usually reserved for cases with poor potential after failure of multiple surgeries. Finally, micropulse trans-scleral diode laser was recently introduced as a viable alternative cyclodestructive procedure that has a higher safety profile with satisfactory efficacy 85, 86, 87. However, its efficacy is often transient and several sessions may be necessary 85, 86, 87…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…In a study of 36 pediatric glaucoma eyes, Elhefney et al reported that IOP was reduced from 37.5 mmHg to 20.0 mmHg, and medications reduced from 2.6 to 1.7, 15 months after MP-TLT. 51 Sixty-six percent of eyes required a second treatment session to maintain control of IOP, and no major complications were observed in any patients. 51 Notably, Abdelrahman et al compared CW-TSCPC and MP-TLT in a cohort of pediatric refractory glaucoma patients.…”
Section: Micropulse Transscleral Laser Treatment (Mp-tlt)mentioning
confidence: 84%
“…51 Sixty-six percent of eyes required a second treatment session to maintain control of IOP, and no major complications were observed in any patients. 51 Notably, Abdelrahman et al compared CW-TSCPC and MP-TLT in a cohort of pediatric refractory glaucoma patients. With success defined as an IOP between 5 and 21 mmHg in the absence no vision-threatening complications at 6 months, the authors reported a greater success rate in the MP-TLT (71%) group compared to the CW-TSCPC (46%) group, however, this difference was not statistically significant.…”
Section: Micropulse Transscleral Laser Treatment (Mp-tlt)mentioning
confidence: 84%